Analysis of Organizational Communication Climate during the COVID-19 Pandemic at SMK Grafika Desa Putera - Hotmaida Marttianno Nainggolan; Ahmad Toni (Persepsi: Communication Journal, 2022)
Human interaction in society which then forms a group with the same goal will eventually give birth to an organization. A good organization can be seen from members in each section working systematically so that they are able to achieve the goals of the organization. A good organization will also create a warm atmosphere for all members of the organization. One of the things that affect the condition of an organization is the organizational communication climate, which is the perceptions between the elements of the organization and the influence of these elements in communication. There are five basic elements of the organization, such as organizational members, work in the organization, management practices, organizational structure and guidelines. This study aims to analyze the organizational communication climate at SMK Grafika Desa Putera during the COVID-19 pandemic and the factors that influence it. The research was conducted from January to December 2021. This research used a quantitative approach accompanied by qualitative analysis so as to deepen the results of the analysis achieved. The survey method was used to obtain premier data and participant observation methods as well as in-depth interviews with purposive respondents were used to strengthen the premier data. While the data analysis technique used an ordinal scale from the data distributed through a questionnaire and then coded into a distribution table for the analysis of one variable.